2021
DOI: 10.1159/000521438
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious Effect of Crossfostering in Rat Pups on Hypoxic-Ischaemic Injury Tolerance and Hypothermic Neuroprotection

Abstract: We study the effect of hypothermia (HT) following hypoxic-ischemic (HI) brain injury in postnatal day 7 (P7) rats. In 2015, new European Union animal transport regulations prompted a change in practice at the breeding facility, which henceforth crossfostered P3 litters to P8 older lactating dam prior to transportation. It is generally assumed that crossfostering does not significantly affect the experimental results. The aim of this study was to examine whether crossfostering affects our model consistency by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…We controlled for this by matching the non‐probe controls to each skin and rectal probe. Moreover, 34% of the litters analyzed were crossfostered by an older dam, which we recently reported to exacerbate HI injury in a mild Vannucci model (Gundersen, Menassa, et al, 2021 ). However, in the current study we found no significant difference between crossfostered and non‐crossfostered rats, presumably due to the longer insult duration (90 min) diminishing this effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We controlled for this by matching the non‐probe controls to each skin and rectal probe. Moreover, 34% of the litters analyzed were crossfostered by an older dam, which we recently reported to exacerbate HI injury in a mild Vannucci model (Gundersen, Menassa, et al, 2021 ). However, in the current study we found no significant difference between crossfostered and non‐crossfostered rats, presumably due to the longer insult duration (90 min) diminishing this effect.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve a sufficient sample size of probe rats, we collected data from 23 experiments previously published and conducted in the Oslo laboratory between 2013 and 2016 (Wood et al, 2020 ). Thirty‐four percent of the litters were crossfostered (Gundersen, Menassa, et al, 2021 ). Each experiment was conducted on a set of five or six litters of ten pups each exposed to hypoxia in one large chamber with 60 individual partitions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation